KEDUDUKAN SAKSI MAHKOTA SEBAGAI ALAT BUKTI DALAM PRAKTIK PERADILAN PIDANA - , AMRULLAH, S.HI ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The practice of criminal justice is a process over the application of criminal procedural law in accordance with the rules that already exist in the Book of Law Code of Criminal Procedure (Criminal Procedure). But in practice many things that are not regulated in the Criminal Code but in practice continued in use as well as the application of crown witnesses. Therefore the focus of study in this research is what the basic consideration of the use of crown witnesses in criminal justice practices, how the position of fiber crown witness in the criminal justice practices. The research method used in this study in normative and empirical, using the data in the field as the primary data to address existing problems, along with secondary data such as regulatory legislation and the literature of library research. Techniques of data collection using interviews with respondents selected by purposive sampling technique. Descriptive analysis is used in analyzing the data in this study. The result of this study indicate that the basic consideration of the use of crown witnesses in criminal justice practice are the first, there is no ban on the use of crown witnesses in the Criminal Procedure Code. Second, a crown witness in splitsing justified its use on the aplication (solving the case) based on the rules of Article 142 Criminal Procedure Code. Application of the crown witness has a very important position in a criminal case reveals minimal evidence, especially in the case of inclusion. But in a matter of respect for the crown or crown witnesses are often overlooked as well as the policy is up from the judge, its caused by the absence of rules that mention the crown (the award) is how that should be given to the crown witnesses.